Propriedades biológicas das proteínas Galectina-3 e rP21 na infecção por Trypanosoma cruzi in vitro e in vivo - Silva, Aline Alves da (2019)
Trypanosoma cruzi is a flagellate protozoan and etiological agent of Chagas' disease. It is estimated the existence of 6 to 7 million infected people in the world, being the Chagas' heart disease the main manifestation of the disease. Galectin-3 (Gal-3) is one of the proteins that has increased expression during infection. This protein belongs to the lectin family, has affinity for carbohydrates containing β-galactosides and is involved in several biological events such as cell adhesion, cell cycle regulation, apoptosis, intracellular signaling and immune response. P21 is a protein secreted by T. cruzi, is related to the parasite evasion of the host immune response and guarantees the permanence of T. cruzi in the intracellular environment. From this, the aim of this study was to evaluate the biological activities of Gal-3 and recombinant protein P21 (rP21) during T. cruzi infection. In this sense, Wild-type (WT), galectin-3 knockout (Gal-3 KO) and galectin-3 knockdown (Gal-3 KD) cells infected with T. cruzi were used for analysis of intracellular multiplication, cell lysis and number of extracellular parasites. The data presented here demonstrated that the absence or reduced expression of Gal-3 resulted in high intracellular replication rates, increased cell lysis and increased number of extracellular parasites. Subsequently, WT and Gal-3 KO mice were infected for 90 days and cardiac tissue was removed for staining with Picrosirius Red and RT-PCR in real time. Comparing these groups, we observed increased fibrosis in infected Gal-3 KO animals. In addition, using the RT-PCR methodology we noted the decrease in the expression of the CXCR4 chemokine receptor in these animals. Observed this scenario, we tested the relationship of the lower expression of CXCR4 and the main biological activities of the receptor related to infection control. For this, we used the rP21, which binds to the CXCR4 receptor and activates the PI3K signaling pathway, and thus exerts several functions such as induction of actin cytoskeleton polymerization, prophagocytic and chemotactic activity. WT and Gal-3 KO peritoneal macrophages treated or not with rP21 were used for actin polymerization analysis on flow cytometer by phalloidin-TRITC labeling, chemotaxis assay using Transwell system and parasite multiplication assay. We have seen that the absence of Gal-3 led to the reduction of actin polymerization and chemotaxis, probably due to the reduced expression of the CXCR4 receptor in these cells. We studied by ELISA the positive sera for infection by T. cruzi and we observed that these can present specific antibodies against P21. In addition, rP21 is a promising protein for the development of therapeutic targets during the acute phase of intense parasitic multiplication. It can be studied for these purposes, as it did not present cytotoxicity and did not promote the formation of a clot in plasma. Therefore, we report the importance of the host Gal-3 and the T. cruzi P21 for actin polymerization, cell recruitment and parasite multiplication control. Thus, these components benefit both the host and the parasite, since they decrease the intense multiplication, guarantee the survival of the host and favor the parasitic perpetuation.